PEMANFAATAN INFORMASI AKUNTANSI SEBAGAI ALAT REPOSISI UMKM DALAM MENGHADAPI COVID-19 - Devi Febrianti; Ninik Mas’adah; Amrizal Imawan (Media Mahardhika, 2022)
Business actors must readjust their predetermined strategies with the current COVID-19 pandemic conditions. At least UMKM players are able to ensure finances, stay healthy, and can survive this difficult time. Therefore, to restructure MSME strategies in dealing with COVID-19 conditions, business actors must prepare financial reports or accounting information as a basis for making economic decisions.This research was conducted in a group of successful and prosperous UMKM businesses in Sidayu District, Gresik Regency. This community houses around 50 MSME players in the northern part of Gresik Regency (Pantura). This study aims to understand the practice of using accounting information as a means of repositioning MSMEs in dealing with COVID-19 in Gresik Regency.This research uses qualitative research using an interpretive paradigm so that the data obtained must be in-depth, clear, and specific. In this study, researchers used data techniques by distributing questionnaires and interviews. The results of this study indicate that several MSMEs studied have used accounting information to take business actions and decisions in accordance with accounting theory. They also said that in running a business, financial reports have an important role in developing their business.